Nursing Approaches for the Prevention and Care of Delirium in Older Adults Undergoing Surgery - Sangarunakul, Nipaporn; Thikom, Napat (The Journal of Chulabhorn Royal Academy, 2025)
Delirium is a common neurological complication in hospitalized older adults, particularly those undergoing surgery or experiencing acute illness. This condition significantly impacts both physical and mental health, leading to prolonged hospital stays, an increased risk of complications, cognitive decline, and higher mortality rates. This article aims to review and synthesize nursing knowledge related to the prevention and management of delirium in this population. It focuses on patient characteristics, clinical manifestations, types of delirium, predisposing and precipitating risk factors, standard screening tools such as 4AT and CAM-ICU, and nursing approaches throughout perioperative care. The article also highlights system-level management strategies within hospital wards to promote safe and continuous care. Nurses play a vital role in risk assessment, screening, monitoring, and delivering proactive care to prevent, mitigate, and reduce the impact of delirium, thereby enhancing care quality and achieving tangible positive outcomes for hospitalized older adults.